2014
DOI: 10.1111/cod.12320
|View full text |Cite
|
Sign up to set email alerts
|

Are gloves sufficiently protective when hairdressers are exposed to permanent hair dyes? An in vivo study

Abstract: Many protective gloves used by hairdressers are unsuitable for protection against the risk of elicitation of allergic contact dermatitis caused by PPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Moreover, both hairdressers and hairdressing trainees often reuse single‐use disposable gloves, and there is a lack of knowledge about which types of gloves are adequate for the hairdressing sector with regard to hairdressers’ protection from wet work and chemicals, and protection of customers from unpleasant tension or picking of the hair. Nitrile gloves proved to be adequate in both regards …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, both hairdressers and hairdressing trainees often reuse single‐use disposable gloves, and there is a lack of knowledge about which types of gloves are adequate for the hairdressing sector with regard to hairdressers’ protection from wet work and chemicals, and protection of customers from unpleasant tension or picking of the hair. Nitrile gloves proved to be adequate in both regards …”
Section: Discussionmentioning
confidence: 98%
“…Nitrile gloves proved to be adequate in both regards. 32 Another existing obstacle is that, whereas tackling insufficient prevention of work-related skin diseases is a top-priority problem in Europe, common standards for the prevention of these conditions are lacking. 6 After a Cochrane Database Systematic review regarding interventions for preventing occupational irritant hand dermatitis, it was concluded that, at present, there is insufficient evidence to enable confident assessment of the effectiveness of interventions used in primary prevention.…”
Section: Skin Symptoms and Tewlmentioning
confidence: 99%
“…The nitrile gloves gave good protection, even after 60 min of exposure to the hair dye. Many protective gloves used by hairdressers were found to be unsuitable for protection against the risk of elicitation of allergic contact dermatitis caused by PPD [33].…”
Section: Management and Preventionmentioning
confidence: 99%
“…The latter finding is unlikely to be related to the glove material or duration of exposure, given that 0.04 mm nitrile gloves have been shown to afford good protection against 0.9% PPD for 60 min6 and against 5% PPD for >4 h 4 5. Nor is it likely related to glove technique, which was optimised in all participants.…”
mentioning
confidence: 97%
“…Both in vitro and in vivo studies have demonstrated the efficacy of gloves in reducing both dermal and systemic exposure to hair dye compounds 4 5. Use of disposable nitrile gloves is recommended 6. However, the protective capacity of gloves has not previously been demonstrated in a real-work hairdressing setting.…”
mentioning
confidence: 99%